Enhancing employee competitiveness: The role mediation of human resources competencies - Sismiati, Sismiati; Sulaiman, Syarifuddin; Usmar, Usmar; Tamrin Lanori; Susanto, Primadi Candra (Goodwood Publishing, 2025)
Purpose: Effective methods for digital literacy and financial management are expected to enhance HR competency and employee competitiveness in the job market. Research Methodology: This quantitative study used SEM-PLS with convenience sampling to select 192 BUMD employees in DKI Jakarta. Data were collected via an online Likert-scale questionnaire. Results: This study highlights the role of digital literacy and financial management in HR markets mediated by HR competency. It offers empirical evidence and a framework that integrates these factors to enhance HR competitiveness. Conclusions: This study emphasizes the impact of digital literacy and financial management on HR competencies and organizational competitiveness. This study provides empirical evidence and a framework for enhancing HR capabilities. Limitations: This study was limited by convenience sampling, self-reported data bias, and cross-sectional design. It focuses only on digital literacy and financial management, excluding factors such as leadership and organizational culture. Contribution: This study empirically highlights the role of digital literacy and financial management in enhancing HR competency and competitiveness. It introduces a new framework, offers practical insights, and validates relationships using PLS-SEM.